Efektivitas Model Project-Based Learning dalam Kurikulum Merdeka untuk Meningkatkan Higher-Order Thinking Skills di Sekolah Menengah Atas - Winda Rosida Maulana; Fathiya Ayu Ramadhina; Ichsan Fauzi Rachman (Jurnal Penelitian Pendidikan Indonesia (JPPI), 2025)
This study aims to determine the Effectiveness of the Project-Based Learning (PJBL) Model in the Independent Curriculum to Improve Higher-Order Thinking Skills in Senior High Schools. This study is a analysis descripative study using a literature review method obtained from ten or more journal articles searched by analyzing more than ten scientific journal articles systematically selected from Google Scholar and other trusted sources. The results of the study showed that the implementation of PjBL as a whole had a positive influence and was able to improve students' HOTS in learning science at the Senior High School (SMA) level with an Effect Size of 0.65 in the medium category. This shows that PjBL is one of the Solutions in implementing science learning to improve students' HOTS.